PERAN KELOMPOK WANITA TANI (KWT) TERHADAP PEMBERDAYAAN EKONOMI DESA DI KABUPATEN SRAGEN - Retna Dewi Lestari; Rahmawati Setiyani; Nastiti Winahyu; Sari Fajeri (Agros Journal of Agriculture Science, 2023)
The purpose of this study is to analyze the role of KWT on village economic empowerment. Qualitative and quantitative research was conducted by statistically examining the role of farmer groups in village economic empowerment. The number of respondents determined by the researcher was 50 female farmer respondents assuming they had met the normal distribution statistically. The technique of taking respondents purposively (deliberately) with several criteria including 50 peasant women are members of the farmer women group from KWT Tani Mulyo and KWT Sari Rejeki. The research instrument in the form of questions using the Guttman scale was then categorized qualitatively and tested using the Spearman Rank Correlation. The results showed that the role of KWT in village economic empowerment in Sragen Regency was qualitatively categorized into high and moderate high categories. The role of KWT in village economic empowerment in Sragen Regency in the high category (High Association) is shown by the increase in the ability of farmer women to manage their farms through vegetable cultivation with a hydroponic system. The role of KWT in improving the family economy, helping to open new productive business opportunities through the production of herbal medicine, and helping to empower mothers to be independent and independent in the moderate high category (moderately high association). The role of KWT on village economic empowerment was also analyzed by quantitative methods using the Spearman Rank correlation test. The results show that there is a relationship between the role of KWT on village economic empowerment in Sragen Regency (0.005 value less than 0.05) so that the results of hypothesis testing are reject Ho and accept Ha. The value of Spearman's Rho is 0.388. The value shows that the direction of the relationship between the role variable of KWT and the variable of village economic empowerment is positive, and shows the strength of the weak relationship. This is because not all women farmer members participate in KWT activities and are able to adopt the knowledge and knowledge gained from KWT. Keywords: KWT; Farmer Women; Village EmpowermentINTISARITujuan penelitian ini adalah untuk menganalisis peran KWT terhadap pemberdayaan ekonomi desa. Riset penelitian kualitatif dan kuantitatif dilakukan dengan menguji secara statistik peran kelompok tani terhadap pemberdayaan ekonomi desa. Jumlah responden yang ditetapkan oleh peneliti adalah 50 responden wanita tani dengan asumsi telah memenuhi distribusi normal secara statistika. Teknik pengambilan responden secara purposive (sengaja) dengan beberapa kriteria diantaranya adalah 50 wanita tani merupakan anggota kelompok wanita tani dari KWT Tani Mulyo dan KWT Sari Rejeki. Instrument penelitian berupa pertanyaan dengan menggunakan skala Guttman kemudian dikategorikan secara kualitatif dan diuji dengan menggunakan Korelasi Rank Spearman. Hasil penelitian menunjukkan  Peran KWT terhadap pemberdayaan ekonomi desa di Kabupaten Sragen secara kualitatif dikategorikan menjadi kategori tinggi dan moderate tinggi. Peran KWT dalam pemberdayaan ekonomi desa di Kabupaten Sragen dalam kategori yang tinggi (High Association) ditunjukkan dengan adanya peningkatan kemampuan wanita tani dalam mengelola usahataninya melalui budidaya sayuran dengan sistem hidroponik. Peran KWT dalam menaikkan perekonomian keluarga, membantu membuka peluang usaha baru yang produktif melalui produksi jamu herbal, dan membantu memberdayakan ibu-ibu agar mandiri dan berdikari dalam kategori moderate tinggi (moderately high association). Peran KWT terhadap pemberdayaan ekonomi desa juga dianalisis dengan metode kuantitatif menggunakan uji korelasi Rank Spearman. Hasil menunjukan bahwa terdapat hubungan antara peran KWT terhadap pemberdayaan ekonomi desa di Kabupaten Sragen (nilai 0.005 kurang dari 0.05) sehingga hasil pengujian hipotesis adalah tolak Ho dan menerima Ha. Nilai Spearman’s Rho yaitu sebesar 0.388. Nilai tersebut menunjukkan bahwa arah hubungan variabel peran KWT dan variabel pemberdayaan ekonomi desa bernilai positif, dan menunjukkan kekuatan hubungan yang lemah. Hal ini disebabkan karena anggota wanita tani tidak semua yang berpartisipasi dalam kegiatan KWT dan mampu mengadopsi pengetahuan dan ilmu yang didapatkan dari KWT. Kata kunci: KWT, wanita tani, pemberdayaan desa